А) (х+1)(х+2)-(х+3)(х+4)=0 б) 10х^2-(2x-3)(5x-1)=31 в) (x-2)(x-3)-(x+1)(x-4)=0 г) 12x^2-(4x-3)(3x+1)=-2 Решите уравнение

2

Ответы и объяснения

2013-05-22T16:19:28+00:00
Лучший Ответ!
2013-05-22T16:40:38+00:00

а)(х+1)(х+2)-(х+3)(х+4)=0

х в квадрате+х+2х+2-(х в квадрате+3х+4х+12)

х в квадрате+х+2х+2-х в квадрате-3х-4х-12=0

-4х-10=0

-4х=10

х=-2.5

б)10х в квадрате-(2х-3)(5х-1)=31

10х в квадрате-(10х в квадрате-15х-2х+3)=31

10х в квадрате-10х в квадрате+15х+2х-3-31=0

17х-34=0

17х=34

х=2

в)(х-2)(х-3)-(х+1)(х-4)=0

х в квадрате-2х-3х+6-(х в квадрате+х-4х-4)=0

х в квадрате-2х-3х+6-х в квадрате-х+4х+4=0

-6х+4х+10=0

-2х+10=0

-2х=-10/:(-)2

х=5

г)12х в квадрате-(4х-3)(3х+1)=-2

12х в квадрате-(12х-9х+4х-3)=-2

12х в квадрате-12х+9х-4х+3=-2

5х+3=-2

5х+3+2=0

5х+5=0

5х=-5/:5

х=-1